The Government's Strategy and Efforts to Eradicate Corruption in Indonesia - Muhammad Nasir (Indonesian Journal of Multidisciplinary Science, 2022)
This study identifies corrupt behavior based on the terminology, the Government's efforts to eradicate corruption in Indonesia. However, the most important thing to reduce the level of corruption in Indonesia is the prevention of corruption. This can be done, among others, through concepts, programs to legislative products. The National Integrity System for preventing corruption in Indonesia can run optimally. Factors that cause the High Abuse of Corruption in Indonesia. Internal factors. The causes of corruption in internal factors are: Greed or greedy nature possessed by humans. Humans are not easily satisfied with what they have today. External factors include: Politics where political factors influence the occurrence of corruption because basically politics itself is related to power. The results show that corruption is an act to enrich themselves, their families, groups, and corporations by violating the rules, violating norms. The cause of corruption is individual motivation and a bad government organizational system, and the influence of corruption will increase if it is supported by an environment where bad individuals and systems exist. Based on the above, the strategy that can be taken by the Government of Indonesia is to immediately carry out a Memorandum of Understanding with law enforcement agencies; all financial transactions in government using electronic or online transactions; the government establishes a task force for eradicating extortion in the government; enforce financial reporting on officials in the scope of government; open access to public monitoring through electronic databases; and integrity pact-based performance measurement.